MODERN METHODS OF PHYSICAL REHABILITATION CHILDREN WITH FLAT FEET - Шеіна, М. В.; Нестерчук, Н. Є. (Rehabilitation and Recreation, 2021)
The article discusses the problem of flat feet and its consequences for the childʼs health. The essence of the concept of "flat feet" is revealed, the types of flat feet are characterized, recommendations for prevention of flat feet and improvement of patients health are offered. Preserving and strengthening the health of the younger generation is one of the priorities of our state. Most diseases are instilled in childhood, so to preserve the health of the nation it is necessary to pay close attention to the physical education of children and adolescents. It is important to timely identify children with health disorders that are not yet irreversible, but reduce physical performance, delay the development of the body. Various pathologies of the musculoskeletal system are becoming more common, among which one of the leading places is flat feet. The peculiarity of flat feet is its steady progression, as evidenced by the results of annual reports of the Ministry of Health of Ukraine and special mass scientific research. Acquainted with the latest methods of physical therapy: biomechanical electrical stimulation, vibroplatforms, kinesiotherapy, stato-dynamic taping. Methods of prevention and correction of flat feet among children were considered. Considered how the presence of flat feet affects the professional achievements of athletes and servicemen. Jumping exercises on a soft support are a way to strengthen the arches of the feet in addition to exercise, games are used. Complex physical therapy for flat feet has been developed. The article is recommended for physical therapists, orthopedists, physiotherapists.